Perillaldehyde reduces mitochondrial oxidative stress damage by regulating KCNT2/NR1D1 protein activity in vascular dementia rats - Qian-qian Wang; Hong-dou Zhang; Pei-yao Liu; Chun-rui Zhang; Bao-yue Cui; Xi-yue Li; Meng-yao zhao; Jin-he Yang; Peng Li; Ya-ling Yin; Xue-yu Sun (Molecular Biology Reports, 2026)

White mica as an exploration vector for Archean gold deposits: Integration of in-situ chemistry and SWIR spectroscopy at Kanowna Belle and Sunrise Dam, Western Australia - Yi-Hao Liu; Rui Wang; Dan-Ya Zhou; Yun Zhao (Journal of Geochemical Exploration, 2026)

Temperature-responsive topology regulation for fire-safe, high-strength polyamide 66 via a low-barrier phosphonate spacer - Qin Zhang; Guo-Rui Zhu; Xiang-Xin Xiao; Ya-Dong Wang; Li Chen; Bo-Wen Liu; Yu-Zhong Wang (Chemical Engineering Journal, 2026)

Waste akebiae trifoliata-derived WO3 hierarchical tubes efficient detection of ppb-level triethylamine gas at low temperature and application in food freshness detection - Wen-Xiao Li; Jia-Wang Wang; Rui-Long Li; Qiu-Yue Zheng; Bao-Yu Song; Bo-Ya Liu; Li-Xia Zhao; Ying Fu; Ying-Ming Xu (Chemical Engineering Journal, 2026)

Antioxidant Activity of Bioactive Peptides Derived from Ulva prolifera in HaCaT Cells and Zebrafish - Li-Ru Hong; Shuo-Qi Wang; Ting-Ting Wu; Zhi-Ru Chen; Mo Chen; Chun-Er Cai; Pei-Min He; Ya Zhao; Rui Jia (Marine Biotechnology, 2026)

Algae-bacteria alleviate GHG emissions by oxidation barrier, carbon-iron cycle, microbial community restructuring in Northeast China Mollisol paddy fields - Ze-Wei Qi; Lei Wang; Ya-wei Shi; Rui Guan; Lei Wang; Ying Zhang (Agriculture, Ecosystems & Environment, 2026)

Delta-Band Dynamics of CaMKI-Positive Preoptic Neurons Encode Thermal Homeostatic Information - Dian-Dian Wang; Run-Zhou Yang; Song-Tang Sun; Ya-Lun Sun; Rui-Yu Wang; Xiao-Yan Meng; Sen-Miao Li; Jia-Kang Li; Pei-Pei Liu; Shu-Ang Li; Jian-Sheng Kang (Neuroscience Bulletin, 2026)

Single-cell transcriptomic analysis identifies a MIF-driven keratinocyte-macrophage-Th2 axis as a key inflammatory circuit in atopic dermatitis - Yan Wei; Rui-Min Bai; Hao-Ran Guo; Jin Shan; Li-Juan Wang; Yan Zhou; Kuan-Hou Mou; Yan Zheng; Ya-Guang Zhang (Inflammation Research, 2026)

Undescribed triterpenoid ellagitannins from Castanopsis calathiformis and their potential antiproliferative and hypoglycemic activity - Ya-feng Wang; Ying-rong Bao; Rui-jie He; Nao Pang; Zhang-bin Liu; Bing-yuan Yang; Gui-qin Li; Yong-lin Huang (Phytochemistry, 2026)

How to make big data accessible to plant biologists and beyond: Ten years of lessons from TBtools - Junting Feng; Chengjie Chen; Ya Wu; Longjiang Fan; Zhang Zhang; Ming Chen; Haibao Tang; Guangchuang Yu; Jian Ren; Jingchu Luo; Yi Liao; Aiping Luan; et al. (Molecular Plant, 2026)

Environmental cadmium drives placental senescence and fetal growth restriction via activating CLPP-dependent mitochondrial stress - Rui Pan; Jin Zhang; Lan-Lan Wu; Cheng-Fang Sun; Xin-Xin Zhang; Yu-Xi Wu; Xu-Ai Yin; Ye-Xin Luo; Si-Ting Liu; Zi-Jian Bao; Wei Chang; Ling-Li Zhao; et al. (Journal of Hazardous Materials, 2026)

A versatile colorimetric array sensor based on FeCu-based prussian blue analogue heterostructures for efficient discrimination of tetracycline antibiotics and rapid identification of urinary tract infection pathogens - Dan Wu; Xin-Yu Cheng; Chao-Man Wang; Ya-Nan Kong; Shu-Chang Zhao; Rui-Lin Liu (Journal of Hazardous Materials, 2026)

The potential mechanism of nitrous oxide accumulation in wastewater treatment plants under different load conditions - Wen-Jiao Sang; Bing Gong; Chong-Yang Xing; Bei-Bei Chen; Zhi-Lin Zhang; Hui-Min Fu; Ya-Song Chen; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Yu-Lin Wang; Qiang Wang; et al. (International Biodeterioration & Biodegradation, 2026)

Molecular characterization of a novel partitivirus isolated from Fusarium solani, the causal agent of tobacco root rot - Xiao Wu; Ying Wang; Rui Guo; Ya Rong Wang; Si Jun Li; Xiang Ping Zhou; Jie Zhong; Yan Song Xiao; Tian Bo Liu (Archives of Virology, 2026)

Improved eradication of apple stem grooving virus and apple chlorotic leaf spot virus in apple rootstocks by combining thermotherapy with electrotherapy - Xiao-Yan Ma; Qing Li; Zhi-Wei Kang; Ming-Yuan Jing; Ya-Ting Zhang; Min-Rui Wang; Dong Zhang; Lu Bao; Juan-Juan Ma (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Enhancing photosynthesis and stress tolerance of the cyanobacterium Nostoc sphaeroides by adaptive laboratory evolution via dry-wet cycles - Zhen Chen; Rui Liu; Yu-Qing Peng; Zhang-Zhuo-Ya Wang; Yong-Qi Yin; Sheng Du; Yu-Jie Jin; Kui Xu; Fei-Fei Li; Wei-Zhi Li; Shan Zhang; Hua-Hua Yue; et al. (Algal Research, 2026)

Dynamic recovery sequence optimization of subway-bus network with constrained reinforcement learning - Shan Liu; Zhenhao Meng; Rui Jiang; Zhengli Wang; Ya Zhang; Ying-En Ge (Transportation Research Part D: Transport and Environment, 2026)

Atmospheric cold plasma-induced structural and functional modifications of quinoa protein isolate under various pH conditions - Ya-Ping Wang; Xiaoqing Li; Lang-Hong Wang; Qinglin Sheng; Rui Wang (Food Structure, 2026)

Qualitative analysis of chemical constituents and study on the biological activity of Polygonum perfoliatum L - Chaochen Yue; Ya Zhang; Juan Xue; Tian Lu; Lei Li; Yanjie Wang; Rui Zhou; Di Gao; Huifang Chai (Natural Product Research, 2026)

Raccoon dog parvovirus NS1 protein antagonizes type I interferon signaling by promoting selective autophagic degradation of IRF3 - Wen-yu Cao; Rui-qi Wang; Jin-yang Zheng; Ping Ma; Bo Hu; Cheng-qi Zhang; Ya-jie Sun; Jia-jia Liu; Ding-rui Guo; Zi-han Zhao; Xin Cao; Xue Bai; et al. (Veterinary Microbiology, 2026)

Effect of roasting on the chemical profiles of white and black sesame seeds during accelerated storage - Hao Liu; Shu-Guang Gao; Ming-Zhe Sun; Mei-Qi Yang; Huai-Yang Cao; Ke-Xin Zhang; Min-Shu Hong; Rui-Fu Cui; Zhao Qin; Hua-Min Liu; Xue-Ya Wang; Zhi-Jie Li (Food Chemistry, 2026)

Integrating Machine Learning and Petrophysical Data for 3D Ore Body Modeling: A Case Study of the Bayan Obo Deposit - Shupeng Lu; Ya Xu; Rui Guo; Song Huang; Qianwen Zhang; Yonggang Zhao; Yun Liu; Jian Wang; Liang Zhao (Pure and Applied Geophysics, 2026)

Coupled effects of straw return practices on soil microbial functional potential and agricultural productivity in Semi-Arid Region - Rui-Zhi Liu; Xiao-Ya Zhao; Li-Jie Wang; Xing Zhang; Shu‑Ping Hu; Ju‑Lin Gao; Xiao‑Fang Yu; Qinggeer Borjigin (Plant and Soil, 2026)

Grain-size controls on quartz OSL sensitivity in fluvial systems: insights from transport mechanisms in the upper Yellow River - Ya Liu; Song-Xi Du; Jia-Fu Zhang; Xue Rui; Yu-He Shen; Jia-Jing Wang; Qing-Hao Ma; Zheng-Hao Gu (Geomorphology, 2026)

Reducing grain arsenic and extracting soil arsenic in paddies by an integrated ridge–furrow and ferrihydrite–PVA membrane system - Jing-Min Yang; Qiao-Rui Ren; Zi-Xin Liu; Xin Wang; Dong-Xing Guan; Ya-Nan Dai; He Pei; Bo Peng; Qin-Bo Qin (Journal of Environmental Sciences, 2026)

Construction of bonded CoAl-LDH/COF-316 hybrid photocatalysts with Z-scheme heterojunction for efficient reduction of diluted CO2 - Chao Fan; Rui-Yao Li; Can-Can Yu; Ya Wang; Yu-Xin Xie; Nan-Nan Zhang; Lu-Hua Shao; Gui-Ling Zhang; Hong Dong; Feng-Ming Zhang (Chemical Engineering Journal, 2026)

A metal-immuno photosensitizer strategy: Iridium(III)-zidovudine conjugate triggering sequential organelle stress and synergizing with PD-L1 inhibitor in oral squamous cell carcinoma - Yi-Ling Li; Peng Wang; Wu-Ya Zhang; Rui Zhou; Jia-Ying Zhou; Jia-Wen Chen; Jia-Yin Wu; Bin Cheng; Cai-Ping Tan; Tong Wu (Chemical Engineering Journal, 2026)

Effect of freezing-induced pectin degradation on the texture stability of strawberry - Ya Wang; Xuehui Cao; Qianyu Li; Rui Nian; Kaiyan You; Jingkai Su; Xuefeng Xiong; Danshi Zhu (Food Chemistry, 2025)

Post-collisional crustal evolution in the central Lhasa block of southern Tibet: Insights from early and late Cretaceous magmatism - Shu-Ya Huang; Lu-Lu Hao; Qiang Wang; Andrew C. Kerr; Wan-Long Hu; Qing-Qing Mo; Mao-Rui Liu; Yue Qi; Wei Dan; Xiu-Zheng Zhang (Lithos, 2025)

Advanced strategies in organoid/organ-on-a-chip for food safety and nutrition - Yiyan Zhou; Feiran Wang; Rui Zhao; Tianyi Huang; Wentao Su; Ya Wen; Zhixian He; Dong Li (Food Research International, 2025)

In/S co-decorated SnSe encapsulated in a dual carbon layer for sodium ion storage - Ya Ru Pei; Yong Jin Xia; Lei Ming Wang; Rui Li; Jun Xi Peng; Xue Jing Yang; Jian Li; Chun Cheng Yang; Qing Jiang (Chemical Engineering Journal, 2025)

Deinococcus lichenicola sp. nov., A Bacterium Isolated from a Lichen Sample - Guo-Hua Chen; Lian-Shuang Xiong; Rui Yang; Shu-Ya Zuo; Qing Yuan; Li-Song Wang; Cheng-Lin Jiang; Xin-Yu Wang; Yi Jiang (Current Microbiology, 2025)

High-resolution source apportionment and spatiotemporal drivers of per- and polyfluoroalkyl substances (PFAS) across China’s largest river-estuary continuum: Toward sustainable management of emerging contaminants - Ya Yang; Lai Wei; Rui Wang; Guohua Zhao; Shouye Yang; Haifeng Cheng; Hualin Wu; Qinghui Huang (Water Research, 2025)

Anti-neuroinflammatory naphthol dimers from the marine-derived fungus Penicillium sp. HQ1-23 - Yuan-Han Xie; Chun-Hong Wang; Rong Wang; Hui Jia; Fei Liu; Zi-Hong Peng; Ya-Hui Zhang; Jun Li; Rui-Yun Yang; Li-Jun Zhang; Wei-Feng Xu (Phytochemistry, 2025)

Unprecedented triterpenes with anti-inflammatory activity from Limax maximus - Ya-feng Wang; Pei-de Tang; Rui-jie He; Zhang-bin Liu; Yong-qiong Wei; Jun Ruan; Bing-yuan Yang; Yong-lin Huang (Journal of Natural Medicines, 2025)

Hydrodynamic and geomorphological responses of tidal flats to extreme climate events - Renzhi Li; Ya Ping Wang; Rui Yuan; Ning Zhao; Bixuan Tang; Zhixuan Feng; Bruno Castelle (Journal of Hydrology, 2025)

Comparative Analysis of Stent-Assisted Versus Non-Stent-Assisted Coiling in the Management of Ruptured Intracranial Aneurysms: A Systematic Review and Meta-Analysis - Yu-Hu Ma; Yong-Lin He; Xiao-Yue Zhang; Rui Shang; Hai-Tao Hu; Ting Wang; Sen Lin; Ya-Wen Pan; Chang-Wei Zhang (Translational Stroke Research, 2025)

Mesenchymal Stromal Cells and Graft-versus-Host Disease: Preclinical and Clinical Studies - Rui Wang; Jingkang Xiong; Qing Xu; Ya Zhou; Shijie Yang; Qingxiao Song; Xiaoqi Wang; Xi Zhang (Stem Cell Reviews and Reports, 2025)

Nicotianamine facilitates zinc translocation from roots to shoots in the nickel hyperaccumulator Odontarrhena chalcidica - Teng-Hao-Bo Deng; Ya-Zhou Wang; Bing-Lan Mo; Ting Liu; Lei Li; Ye-Tao Tang; Dian Wen; Yong-Dong Huang; Sheng-Sheng Sun; Xu Wang; Rui-Ying Du; Jean-Louis Morel; et al. (Plant and Soil, 2025)

Parapedobacter flavus sp. nov., isolated from padding of fermentation bed - Rui Wang; Yan-Yan Zheng; Zi-Xuan Liu; Xuan Zhang; You-Jun Liao; Ya-Jing Yu; Ai-Hua Li (Antonie van Leeuwenhoek, 2025)

Biogeochemical impact on the distribution variations of organophosphorus flame retardants in estuarine area and insight into climate change - Lai Wei; Ya Yang; Hongwen Gao; Rui Wang; Feng Cao; Qinghui Huang (Journal of Hazardous Materials, 2025)

Tenecteplase Plus Butyphthalide for Stroke Within 4.5–6 Hours of Onset (EXIT-BT): a Phase 2 Study - Hui-Sheng Chen; Ming-Rui Chen; Yu Cui; Xin-Yu Shen; Hong Zhang; Jiang Lu; Li-Wei Zhao; Ying-Jie Duan; Jing Li; Ya-Mei Wang; Lian-Qiu Min; Li-Hong Zhao; et al. (Translational Stroke Research, 2025)

The nickel hyperaccumulator Odontarrhena chalcidica (Brassicaceae) preferentially takes up zinc over nickel - Ya-Zhou Wang; Ke-Rui Geng; Bing-Lan Mo; Ting Liu; Ye-Tao Tang; Dian Wen; Fu-Rong Li; Xu Wang; Lei Li; Rui-Ying Du; Antony van der Ent; Teng-Hao-Bo Deng; et al. (Plant and Soil, 2025)

Helicobacter pylori VacA-induced gastric mucosal atrophy: a comparative analysis with other forms of atrophic gastritis - Yang-Kun Wang; Wen-Rui Chen; Ling-Yan Lu; Ying-Ying Li; Rui-Kun Qiu; Chao-Ya Zhu; Fa-Shun Zhang; Su-Nan Wang; Si-Liang Xu (Journal of Molecular Histology, 2025)

Uncovering the partitioning, transport flux and socioeconomic factors of organophosphate esters in an urban estuary of eastern China - Ya Yang; Lai Wei; Rui Wang; Guohua Zhao; Shouye Yang; Haifeng Cheng; Hualin Wu; Qinghui Huang (Environmental Pollution, 2025)

Characterization of the gut microbiota in drug abuse: prediction, prevention, and personalized medicine to benefit affected populations - Xin Wang; Ya-Jie Yu; Cai Liao; Xiao-Ru Liu; Rui Yu; Yun Wang (EPMA Journal, 2025)

Botryorhodine J, a new anti-MRSA depsidone isolated from endophytic fungus Alternaria alternata Pas11 - Wen-Yuan Li; Cheng-Cheng Hu; Jin-Hai Liu; Heng-Jie Wang; Ling-Pan Lu; Min Qiao; Ya-Ling Jiang; Rui Wu (Natural Product Research, 2025)

Coplanar two-dimensional Cu-MOF with dual-Cu sites for electrocatalytic CO2 reduction to C2H4 - Yu-Peng Han; Zi-Rui Wang; Ya-Yu Yan; Qiao-Hong Li; Ping Shao; Hai-Xia Zhang; Li-Li Han; Fei Wang; Jian Zhang (Chemical Engineering Journal, 2025)

A systematic comparative analysis of ginger-related varieties from three dimensions based on HS-SPME-GC-Q-TOF MS and UHPLC-LTQ-Orbitrap MS - Huan-ya Yang; Lin Yang; Yu-lu Wang; Yun-shu Hu; Yun Li; Hua Qu; Wen-long Wei; Hui-yan Yang; Qi-rui Bi; Jian-qing Zhang; De-an Guo (Food Research International, 2025)

Lung proteomic and metabolomic changes induced by carbon black nanoparticles and high humidity in a mouse asthma model - Rui Deng; Mingpu Wang; Kian Fan Chung; Ya Zhu (Environmental Pollution, 2025)

One new MOF with hierarchical pores achieving efficient one-step purifying C2H2, recycling CH4 and eliminating CO2 in C2H2 production - Lin Zhang; Ya-Li Bao; Rui-Cheng Gao; Wen-Juan Shi; Yi-Zhao Guo; Lei Hou; Yao-Yu Wang (Chemical Engineering Journal, 2025)

Molecular mechanisms behind the inhibitory effects of ginsenoside Rg3 on hepatic fibrosis: a review - Zhao-feng Tian; Rui-yi Hu; Zi Wang; Ya-jun Wang; Wei Li (Archives of Toxicology, 2025)

Over 200 times current enhancement via buckling triboelectric nanogenerator at ultra-low speed for monitoring the swelling of lithium ion batteries - Maoyi Zhang; Chaosheng Hu; Tongtong Zhang; Chris R. Bowen; Rui Li; YongAn Huang; Yewang Su; Zhong Lin Wang; Ya Yang (Science Bulletin, 2025)

Utilizing large language models for identifying future research opportunities in environmental science - Xiaoliang Ji; Xinyue Wu; Rui Deng; Yue Yang; Anxu Wang; Ya Zhu (Journal of Environmental Management, 2025)

Shear capacity of additively manufactured stainless steel bolted connections after fire - Zhengyi Kong; Rui Li; Xiaofei Wang; Ningning Hu; Ya Jin; Qinglin Tao; George Vasdravellis (Engineering Structures, 2025)

Two novel butyrolactone lignan dimers from leaves of Castanopsis chinensis and their anti-inflammatory activities - Ya-Feng Wang; Ping Lin; Nao Pang; Zhang-Bin Liu; Bing-Yuan Yang; Rui-Jie He; Yong-Lin Huang (Journal of Natural Medicines, 2025)

Leifsonia stereocauli sp. nov., Isolated from Stereocaulon tomentosum Fr. Lichen - Shu-Ya Zuo; Lian-Shuang Xiong; Qing Yuan; Guo-Hua Chen; Rui Yang; Li-Song Wang; Cheng-Lin Jiang; Xin-Yu Wang; Yi Jiang (Current Microbiology, 2025)

Holocene paleoenvironment of the Nihewan Basin, China, inferred from high-resolution luminescence dating and a multiproxy analysis of gully sediments - Qing-Hao Ma; Yu-Jie Guo; Hua-Rui Lei; Yu-He Shen; Jia-Jing Wang; Ya Liu; Zhen-Yu Zhou; Jia-Fu Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Antioxidant and anti-inflammatory activities and action mechanisms of exopolysaccharides from Lactiplantibacillus plantarum Z-1 - Qiong Xu; Miao-Miao Wang; Xinyue Li; Ya-Rui Ding; Xiao-Yi Wei; Tao Zhou (Food Bioscience, 2024)

The inoculation of Bacillus paralicheniformis and Streptomyces thermoviolaceus enhances the lignocellulose degradation and microbial communities during spent mushroom substrate composting - Jiao Zhang; Ya-Jie Zou; Shun-Li Wang; Wei-Wei Zhang; Qing-Jun Chen; Qiu-Ying Wang; Ti-Kun Guan; Jia-Yan Zhang; Min-Rui Zhao; Guo-Qing Zhang (Environmental Research, 2024)

PABPN1 functions as a predictive biomarker in colorectal carcinoma - Qing-hua Wang; Pei-ci Yan; Li-zhou Shi; Ya-jie Teng; Xiao-jiao Gao; Li-qian Yao; Zhi-wei Liang; Ming-hui Zhou; Wei Han; Rui Li (Molecular Biology Reports, 2024)

The LINGO-1-deficient neural stem cell-derived neural tissueoid showed enhanced retention and neuronal relay in the transected spinal cord - Ge Li; Li-Jun Huang; Bao Zhang; Shu Liu; Jing-Hua Liang; Ying Ding; Xiang Zeng; Bi-Qin Lai; Yuan-Huan Ma; Ya-Qiong Wang; Rui Wang; Hong-Bo Zhang; et al. (Chemical Engineering Journal, 2024)

Cuproptosis-Associated lncRNA Gene Signature Establishes New Prognostic Profile and Predicts Immunotherapy Response in Endometrial Carcinoma - Xi-Ya Jiang; Jing-Jing Hu; Rui Wang; Wei-Yu Zhang; Qin-Qin Jin; Yin-Ting Yang; Jie Mei; Lin Hong; Hui Yao; Feng Tao; Jie-Jie Li; Yu Liu; et al. (Biochemical Genetics, 2024)
Uterine corpus endometrial carcinoma (UCEC), a prevalent kind of cancerous tumor in female reproductive system that has a dismal prognosis in women worldwide. Given the very limited studies of cuproptosis-related lncRNAs (CRLs) in UCEC. Our purpose was to construct a prognostic profile based on CRLs and explore its assess prognostic value in UCEC victims and its correlation with the immunological microenvironment.Methods: 554 UCEC tumor samples and 23 normal samples’ RNA-seq statistics and clinical details were compiled from data in the TCGA database. CRLs were obtained using Pearson correlation analysis. Using LASSO Cox regression, multivariate Cox regression, and univariate Cox regression analysis, six CRLs are confirmed to develop a risk prediction model at last.We identified two main molecular subtypes and observed that multilayer CRLs modifications were related to patient clinicopathological features, prognosis, and tumor microenvironment (TME) cell infiltration characteristics, and then we verified the prognostic hallmark of UCEC and examined its immunological landscape.Finally, using qRT-PCR, model hub genes’ expression patterns were confirmed. Results: A unique CRL signature was established by the combination of six differently expressed CRLs that were highly linked with the prognosis of UCEC patients. According to their CRLs signatures, the patients were divided into two groups: the low-risk and the high-risk groups. Compared to individuals at high risk, patients at low risk had higher survival rates ( p

Rare oxoisoaporphine alkaloids from Menispermum dauricum with potential anti-inflammatory activity - Rui Guo; Cun-Lin Wang; Xiao-Juan Cao; Xiao-Juan Yao; Xin Qiao; Ya-Tian Meng; Tong Zhang; Qiong Zhang (Phytochemistry, 2024)

Water–Rock reactions in the acid leaching of Uranium: Hydrochemical characteristics and reaction mechanisms - Bing Wang; Yue Luo; Xun Li; Ya–zhou Liu; Chang–rui Xu; Yu–xiu Zheng; Yan–hong Zhang; Yi–ru Zhou (Journal of Hydrology, 2024)

Effect of immersion freezing on water migration in Huangguan pears - Xuehui Cao; Xiaomin Zhang; Ya Wang; Rui Nian; Kaiyan You; Danshi Zhu (International Journal of Refrigeration, 2024)

PET microplastics influenced microbial community and heavy metal speciation in heavy-metal contaminated soils - Yajuan Tang; Yi Xing; Xin Wang; Haobo Ya; Tian Zhang; Mingjie Lv; Jianchao Wang; Han Zhang; Wei Dai; Duo Zhang; Rui Zheng; Bo Jiang (Applied Soil Ecology, 2024)

Effects of ultrasonic pretreatment on drying characteristics and water migration characteristics of freeze-dried strawberry - Xinyue Zhang; Ya Wang; Rui Nian; Qianyu Li; Danshi Zhu; Xuehui Cao (Food Chemistry, 2024)

Cement-based external wall insulation material with thermal performance improvement by partial substitution of calcium silicate - Wen Rui Ren; Cheng Hai Wang; Chang Bao Han; Dong Han; Jia Yu Zheng; Ya Nan Cui; Xue Mei Song; Quan Jiang; Hui Yan (Energy and Buildings, 2024)

A highly sensitive and colorimetric fluorescent probe for visualizing hydroxylamine in immune cells - Wei Du; Yang Tian; Yu-An Feng; Xiao-Wei Cong; Rui Tan; Ya-Wen Wang; Yu Peng (Analytica Chimica Acta, 2024)

Targeting gut microbiota for immunotherapy of diseases - Ya-Jie Yu; Xiao-Dong Liu; Cai Liao; Rui Yu; Xin Wang; Ming Li; Yun Wang (Archives of Toxicology, 2024)

Impact of high-altitude environments on the motion and settling characteristics of wet-mix shotcrete dust in tunnels - Guoliang Zhang; Zhongan Jiang; Xiaocuan Li; Ya Chen; Bin Yang; Mingli Si; Rui Feng; Ming Wang (Tunnelling and Underground Space Technology, 2024)

Comprehensive analysis of metal(loid)s and associated metal(loid) resistance genes in atmospheric particulate matter - Xiu-Peng Liang; He-Jing Wang; Jie-Ru Zheng; Xiao-Ru Wang; Dao-Ming Lin; Ya-Qing Wu; Rui-Lian Yu; Gong-Ren Hu; Yu Yan (Science of The Total Environment, 2024)

Three new quinic acid derivatives and a new shikimic acid derivative from the leaves of Castanopsis orthacantha - Xue-Xue Cheng; Ya-Feng Wang; Rui-Jie He; Bing-Yuan Yang; Zhang-Bin Liu; Yong-Lin Huang (Phytochemistry Letters, 2024)

Heavy metals potentially drive co-selection of antibiotic resistance genes by shifting soil bacterial communities in paddy soils along the middle and lower Yangtze River - Ya ZHANG; Hao WANG; Minghui HU; Rui CAI; Yuqing MIAO; Xiancan ZHU (Pedosphere, 2024)

Electrochemically assisted preparation of graphitic carbon nitride nanosheet membranes for efficient water purification - Yisa Zhou; Ya Zhang; Jian Xue; Rui Wang; Jiale Dong; Zongjie Yin; Chen Guo; Haihui Wang (Chemical Engineering Journal, 2024)

Stochastic processes shape microbial community assembly in biofilters: Hidden role of rare taxa - Yong-Chao Wang; Ya-Hui Lv; Can Wang; Ye Deng; Yu-Ting Lin; Guan-Yu Jiang; Xu-Rui Hu; John C. Crittenden (Bioresource Technology, 2024)

Chemical constituents from the leaves of Fraxinus hubeiensis, an endemic plant from China - Li-Min Gong; Hong-Xia Tang; Ya-Jie Li; Rui-Ding Wen; Xin-Yi Liu; Yu-Wen Deng; Qing-Lai Wu; Zhi-Feng Zhang; Xu-Dong Zhou; Wei Wang (Biochemical Systematics and Ecology, 2024)

Biotemplated fabrication of N/O co-doped porous carbon confined spinel NiFe2O4 heterostructured mimetics for triple-mode sensing of antioxidants and ameliorating packaging properties - Yuan Gao; Juan Wang; Lin-Lan Zhao; Bo-Yi Yuan; Ya-Nan Kong; Jing-Jing Luo; Shu-Chang Zhao; Wei-Ming Yang; Rui-Lin Liu (Food Chemistry, 2024)

CircRNA: a rising therapeutic strategy for lung injury induced by pulmonary toxicants - Cai Liao; Zhen-Wei He; Rui Yu; Ya-Jie Yu; Xiao-Ru Liu; De-Lei Kong; Yun Wang (Archives of Toxicology, 2024)

Triterpene hexahydroxydiphenoyl ester and phenol glucosides from the leaves of Castanopsis eyrie (Champ. ex Benth.) Hutch - Bing-Yuan Yang; Nao Pang; Rui-Jie He; Ya-Feng Wang; Yong-Lin Huang (Natural Product Research, 2024)

Viologen-based ionic conjugated mesoporous polymer as the electron conveyer for efficient polysulfide trapping and conversion - Hai-Yang Li; Zhong-Shan Li; Gang-Hao Qiu; Rou-Rou Zhang; Ya-Rui Wang; Feng Wang; Ren-Wu Huang; Xiao-Fei Liu; Shuang-Quan Zang (Science Bulletin, 2024)

Pathological and genome assembly of transcriptome sequencing data implied multiple relationships between bean common mosaic virus (BCMV), Batocera lineolata and aphids in Populus alba var. pyramidalis - Min Li; Jinxin Li; Yanxia Yao; Rui Yang; Yuchen Fu; Li Wang; Wanna Shen; Huixiang Liu; Ya Liu; Jiaping Zhao (Physiological and Molecular Plant Pathology, 2024)

Microbial metabolic flexibility guarantees function resilience in response to starvation disturbance - Yong-Chao Wang; Ya-Hui Lv; Xu-Rui Hu; Yu-Ting Lin; John C. Crittenden; Can Wang (Bioresource Technology, 2024)

Potential protective effects of sodium butyrate on glycinin-induced oxidative stress, inflammatory response, and growth inhibition in Cyprinus carpio - Deng-Lai Li; Si-Ying Liu; Rui Zhu; Si-Tong Meng; Yin-Tao Wang; Zhi-Yong Yang; Liang Li; Xiao-Fang Wei; Guo-Jun Shang; Hao-Tong Wang; Zi-Hui Qu; Ya-Nan Quan; et al. (Fish Physiology and Biochemistry, 2024)

New 4',5'-methylenedioxyflavone derivatives from the whole plant of sarcandra glabra - Ya-Qiu Qin; Wei Liu; Rui Yin; Ping-Ting Xiao; Zi-Yuan Wang; Tian-Qing Huang; E-Hu Liu (Natural Product Research, 2024)

Development and evaluation of a bivalent vaccine based on recombinant newcastle disease virus expressing infectious bursal disease virus VP2L-CH3-CH4 in SPF chickens - Wen Ying Sun; Xiao Lin Cao; Yi Xuan Wang; Xiao Chen Guo; Jin Miao Liu; Zhi Qiang Xue; Hui Juan Li; Wei Wang; Ting Ting Zhang; Qianhui Li; Rui Han Qin; Yu Han Jin; et al. (Veterinary Microbiology, 2024)

A review of the strategy to promote microalgae value in CO2 conversion-lipid enrichment-biodiesel production - Huan Liu; Tian-Ji Liu; Hua-Wei Guo; Ya-Jun Wang; Rui Ji; Le-Le Kang; Yi-Tong Wang; Xuan Guo; Jun-Guo Li; Li-Qun Jiang; Zhen Fang (Journal of Cleaner Production, 2024)

Unlocking the potential of N-acetylcysteine: Improving hepatopancreas inflammation, antioxidant capacity and health in common carp (Cyprinus carpio) via the MAPK/NF-κB/Nrf2 signalling pathway - Rui Zhu; Guo-Jun Shang; Bao-Yuan Zhang; Hao-Tong Wang; Liang Li; Xiao-fang Wei; Deng-Lai Li; Zhi-Yong Yang; Zi-Hui Qu; Ya-Nan Quan; Si-Ying Liu; Yin-Tao Wang; et al. (Fish & Shellfish Immunology, 2024)

Sub-Himalayan Mesozoic-Cenozoic tectonic-stratigraphic properties and deformation features in the western limb of Hazara Kashmir syntaxis, Pakistan - Irshad Hussain; Zuo-Chen Li; Misbah Fida; Jabir Hussain; Wakeel Hussain; Xian-Zhi Pei; Ya-Jie Yang; Meng Wang; Rui-Bao Li; Lei Pei; Hao Lin (Arabian Journal of Geosciences, 2024)

The co-regulation of the gut microbiome and host genes might play essential roles in metformin gastrointestinal intolerance - Huixiang Zhang; Jiao Lai; Lihuan Zhang; Wei Zhang; Xun Liu; Qilin Gong; Hongxi Tian; Mingzhi Yang; Tao Yang; Rui Zhao; Dongqing Li; Hehua Huang; et al. (Toxicology and Applied Pharmacology, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Two truxinate derivatives and a phenyldilactone from the leaves of Castanopsis eyrei - Ya-feng Wang; Nao Pang; Zhen-hua Liang; Yong-lin Huang; Rui-jie He; Bing-yuan Yang; Zhang-bin Liu (Natural Product Research, 2023)

TBtools-II: A “one for all, all for one” bioinformatics platform for biological big-data mining - Chengjie Chen; Ya Wu; Jiawei Li; Xiao Wang; Zaohai Zeng; Jing Xu; Yuanlong Liu; Junting Feng; Hao Chen; Yehua He; Rui Xia (Molecular Plant, 2023)

Health benefits of traffic-related PM2.5 and CO reduction—a case study of Tianjin, China, from 2015 to 2019 - Yunqian Chen; Zheng Ran; Ya-nan Wang; Xiaoping Liu; Pu Yang; Kun Han; Xiaoge Yin; Chao Zou; Rui Wu; Hongjun Mao; Taosheng Jin (Air Quality, Atmosphere & Health, 2023)

Multifunctional carboxylated cellulose nanofibers/exfoliated bentonite/Ti3C2 aerogel for efficient oil adsorption and recovery: The dual effect of exfoliated bentonite and MXene - Rui Tang; Ya Hu; Jingyuan Yan; Shiqi Xu; Yinlong Wang; Jinsheng Yan; Dankui Liao; Hanbing Zhang; Zhangfa Tong (Chemical Engineering Journal, 2023)

Megastigmane sesquiterpenoids from Saussurea medusa and their anti-inflammatory activities - Jing-Ya Cao; Qi Dong; Zhi-Yao Wang; Ye Zhao; Yu Ren; Li-Juan Mei; Yan-duo Tao; Rui-Tao Yu (Natural Product Research, 2023)

Insights on rational design and regulation strategies of Prussian blue analogues and their derivatives towards high-performance electrocatalysts - Yu-Rui Ji; Ya-Fei Guo; Xu Liu; Peng-Fei Wang; Ting-Feng Yi (Chemical Engineering Journal, 2023)

Efficient lipid synthesis of Chlorella pyrenoidosa promoted under heavy metals from electric arc furnace slag - Qing Yu; Tian-Ji Liu; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Yu-Ran Wang; Le-Le Kang; Rui Ji; Fu-Ping Wang; Xiao-Man Wang; Bao Liu; Shuang Cai; et al. (Journal of Cleaner Production, 2023)

Two new isoflavones from the barks of Dalbergia hancei Benth - Xiao-Mei Li; Nao Pang; Ya-Feng Wang; Rui-Jie He; Li Ge; Bing-Yuan Yang; Ke-Di Yang; Yong-Lin Huang (Natural Product Research, 2023)

Assessment of radiation doses and DNA damage in pediatric patients undergoing interventional procedures for vascular anomalies - Ya Ma; Lei Guo; Lianying Fang; Dianjun Hou; Rui Chen; Xiaoshan Wang; Xuesong Mao; Zihan Zhao; Yingmin Chen (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2023)

A novel fluorescent probe for imaging endogenous hydrogen sulfide in living cells and mice models of acute liver injury - Kai Wang; Rui Guo; Xu-Yang Chen; Xiu-Lin Li; Zhi-Gang Hu; Xiao Wang; Chao-Yue Wang; Ya-Juan Qin; Kun Yao; Yu-Shun Yang (Chemical Engineering Journal, 2023)

Cytotoxic steroids from the stems of Strophanthus divaricatus - Hong-Ling Ran; Sheng-Zhuo Huang; Hao Wang; Li Yang; Cui-Juan Gai; Rui-Jun Duan; Hao-Fu Dai; Ya-Li Guan; Wen-Li Mei (Phytochemistry, 2023)

Rapid identification of high and low cadmium (Cd) accumulating rice cultivars using machine learning models with molecular markers and soil Cd levels as input data - Zhong Tang; Ting-Ting You; Ya-Fang Li; Zhi-Xian Tang; Miao-Qing Bao; Ge Dong; Zhong-Rui Xu; Peng Wang; Fang-Jie Zhao (Environmental Pollution, 2023)

Photo-assisted thermal catalysis for methanol synthesis from methane oxidation on Cu-MOR/g-C3N4 - Yan-Qun Chen; Rui-Xin Zhang; Miao Ren; Ya-Xin Jin; Wen-Jing Wang; Jia-Yao Feng; Zhi-Hua Gao; Zhi-Feng Yan; Yi-Ming Liu; Wei Huang; Lei Liu; Zhi-Jun Zuo (Fuel, 2023)

Heavy metals in riverine/estuarine sediments from an aquaculture wetland in metropolitan areas, China: Characterization, bioavailability and probabilistic ecological risk - Hai-Song Li; Yang-Guang Gu; Rui-Ze Liang; Ya-Su Wang; Richard W. Jordan; Liang-Gen Wang; Shi-Jun Jiang (Environmental Pollution, 2023)

Parameter Study on How the Cervical Disc Degeneration Affects the Segmental Instantaneous Centre of Rotation - Hong Zhang; Dacheng Sang; Bin Zhang; Ya-Nan Ren; Xin Wang; Jing-Jing Feng; Cheng-Fei Du; Baoge Liu; Rui Zhu (Journal of Medical and Biological Engineering, 2023)

Study on non-point source pollution characteristics under different spatial scales: a case study of Hanjiang River Basin, China - Ya-jiao Li; Jia-ping Wang; Zi-hang Zhang; Gai-rui Hao; Ya-fang Li; Jia-ke Li (Environmental Science and Pollution Research, 2023)

The protective role of vitamin C on intestinal damage induced by high-dose glycinin in juvenile Rhynchocypris lagowskii Dybowski - Rui Zhu; Zongyu Liu; Minghui Lu; Xueqin Wu; Xueyuan Zhao; Hong-He Wang; Ya-Nan Quan; Li-Fang Wu (Fish & Shellfish Immunology, 2023)

A chitin synthase mutation confers widespread resistance to buprofezin, a chitin synthesis inhibitor, in the brown planthopper, Nilaparvata lugens - Bin Zeng; Fu-Rong Chen; Ya-Ting Liu; Di Guo; Yi-Jie Zhang; Ze-Rui Feng; Li-Xiang Wang; John Vontas; Shun-Fan Wu; Kun Yan Zhu; Cong-Fen Gao (Journal of Pest Science, 2023)

Abnormal fatty acid metabolism and ceramide expression may discriminate myocardial infarction from strangulation death: A pilot study - Song-Jun Wang; Bing-Rui Liu; Fu Zhang; Ya-Ping Li; Xiao-Rui Su; Chen-Teng Yang; Bin Cong; Zhi-Hua Zhang (Tissue and Cell, 2023)

Effects of bepridil on early cardiac development of zebrafish - Ya-Lan Wei; Yu-Qing Lei; Zhou-Jie Ye; Xu-Dong Zhuang; Li-Ping Zhu; Xin-Rui Wang; Hua Cao (Cell and Tissue Research, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Influences of subcellular Ca redistribution induced by γ irradiation on the fruit firmness of refrigerated blueberries - Chen Wang; Ye Tao; Yanqiu Han; Rui Zhang; Lifeng Li; Ya Gao (Postharvest Biology and Technology, 2023)

Characteristics and origin of Lower Triassic Feixianguan Formation dolostones on the west side of Kaijiang–Liangping Trough, northeastern Sichuan Basin, China - Ling Zhou; Guangwei Wang; Ya Zhang; Yanping Qiao; Fang Hao; Rui Xu; Li Quan; Ping Wang (Marine and Petroleum Geology, 2023)

Evaluation of LiNiO2 with minimal cation mixing as a cathode for Li-ion batteries - Rio Akbar Yuwono; Fu-Ming Wang; Nae-Lih Wu; Yan-Cheng Chen; Hsi Chen; Jin-Ming Chen; Shu-Chih Haw; Jyh-Fu Lee; Rui-Kun Xie; Hwo-Shuenn Sheu; Po-Ya Chang; Chusnul Khotimah; et al. (Chemical Engineering Journal, 2023)

One-dimensional copper bromide based inorganic-organic hybrids as fuels for hypergolic bipropellants with hydrogen peroxide as oxidizer - Ya-Jie Wang; Xu-Yang Wang; Hong Xu; Wei-Wei Ren; Rui Pang; Li Yang; Wen-Chao Tong; Qian-You Wang; Shuang-Quan Zang (Chemical Engineering Journal, 2023)

Construction of 3D Ni2+-Al3+-LDH/γ-Fe2O3-Cd2+-Ni2+-Fe3+-LDH structures and multistage recycling treatment of dye and fluoride-containing wastewater - Rui Dang; Xiang-Rong Ma; Yun-Peng Zhao; Menjiao Ren; Wei Guo; Yu-Hong Kang; Yong Gao; Shiqing Bi; Wenwen Gao; Hua-Rui Hao; Rui Bai; Yu-Fei Wang; et al. (Chemical Engineering Journal, 2023)

Receptor and Ionic Mechanism of Histamine on Mouse Dorsolateral Striatal Neurons - Jian-Ya Peng; Kang-Li Shen; Xiu-Juan Fan; Zeng-Xin Qi; Hui-Wei Huang; Jian-Lan Jiang; Jian-Hua Lu; Xiao-Qin Wang; Xiao-Xia Fang; Wang-Rui Yuan; Qiao-Xuan Deng; Shu Chen; et al. (Molecular Neurobiology, 2023)

Highly efficient removal of hexavalent chromium by magnetic Fe–C composite from reed straw and electric furnace dust waste - Fu-Ping Wang; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Xi Zhang; Ai-Min Ji; Le-Le Kang; Rui Ji; Qing Yu; Di Gao; Xiao-Man Wang; Zhen Fang (Environmental Science and Pollution Research, 2022)

Three new compounds from the leaves of Castanopsis tibetana Hance - Ya-Feng Wang; Rui-Jie He; Dian-Peng Li; Yong-Lin Huang (Natural Product Research, 2022)

Evaluation of suitable qRT-PCR normalization genes for various citrus rootstocks - Wen He; Rui Xie; Huan Li; Yan Wang; Qing Chen; Yuanxiu Lin; Yunting Zhang; Ya Luo; Yong Zhang; Haoru Tang; Xiaorong Wang (Plant Biotechnology Reports, 2022)

Simvastatin Enhances Muscle Regeneration Through Autophagic Defect-Mediated Inflammation and mTOR Activation in G93ASOD1 Mice - Yafei Wang; Lin Bai; Shuai Li; Ya Wen; Qi Liu; Rui Li; Yaling Liu (Molecular Neurobiology, 2021)

Polymorphisms in the DC-SIGN gene and their association with the severity of hand, foot, and mouth disease caused by enterovirus 71 - Ya-Ping Li; Mu-Qi Wang; Chen-Rui Liu; Hui-Ling Deng; Yuan Wu; Shuang-Suo Dang; Li-Hong Xu (Archives of Virology, 2021)

Change detection in SAR images based on superpixel segmentation and image regression - Rui Zhao; Guo-Hua Peng; Wei-dong Yan; Lu-Lu Pan; Li-Ya Wang (Earth Science Informatics, 2021)

Astrocyte-Derived Lactate Modulates the Passive Coping Response to Behavioral Challenge in Male Mice - Ya-Nan Yin; Jian Hu; Yi-Li Wei; Ze-Lin Li; Zhou-Cai Luo; Rui-Qi Wang; Ke-Xin Yang; Shu-Ji Li; Xiao-Wen Li; Jian-Ming Yang; Tian-Ming Gao (Neuroscience Bulletin, 2021)

Cytokinin (6-benzylaminopurine) elevates lignification and the expression of genes involved in lignin biosynthesis of carrot - Ahmed Khadr; Ya-Hui Wang; Rong-Rong Zhang; Xin-Rui Wang; Zhi-Sheng Xu; Ai-Sheng Xiong (Protoplasma, 2020)

Prefrontal Nectin3 Reduction Mediates Adolescent Stress-Induced Deficits of Social Memory, Spatial Working Memory, and Dendritic Structure in Mice - Hong-Li Wang; Ji-Tao Li; Han Wang; Ya-Xin Sun; Rui Liu; Xiao-Dong Wang; Yun-Ai Su; Tian-Mei Si (Neuroscience Bulletin, 2020)
Chronic stress may disrupt the normal neurodevelopmental trajectory of the adolescent brain (especially the prefrontal cortex) and contribute to the pathophysiology of stress-related mental illnesses, but the underlying molecular mechanisms remain unclear. Here, we investigated how synaptic cell adhesion molecules (e.g., nectin3) are involved in the effects of adolescent chronic stress on mouse medial prefrontal cortex (mPFC). Male C57BL/6N mice were subjected to chronic social instability stress from postnatal days 29 to 77. One week later, the mice exposed to chronic stress exhibited impaired social recognition and spatial working memory, simplified dendritic structure, and reduced spine density in the mPFC. Membrane localization of nectin3 was also altered, and was significantly correlated with behavioral performance. Furthermore, knocking down mPFC nectin3 expression by adeno-associated virus in adolescent mice reproduced the stress-induced changes in behavior and mPFC morphology. These results support the hypothesis that nectin3 is a potential mediator of the effects of adolescent chronic stress on prefrontal structural and functional abnormalities.

Effects of structural planes on rockburst position with respect to tunnel cross-sections: a case study involving a railway tunnel in China - Lei Hu; Xia-Ting Feng; Ya-Xun Xiao; Rui Wang; Guang-Liang Feng; Zhi-Bin Yao; Wen-Jing Niu; Wei Zhang (Bulletin of Engineering Geology and the Environment, 2020)

The stability and pressure behavior characteristics of a special L-type face end formed by low-pressure mining technology without pre-driving roadway - Ya-jun Wang; Jun Yang; Man-chao He; Rui-feng Huang; Xi-chun Tian; Jian-ning Liu; Hao-jie Xue (Arabian Journal of Geosciences, 2020)

Application of metagenomic next-generation sequencing for bronchoalveolar lavage diagnostics in critically ill patients - Ying Li; Bing Sun; Xiao Tang; Ya-lan Liu; Hang-yong He; Xu-yan Li; Rui Wang; Fei Guo; Zhao-hui Tong (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Development of a colloidal gold-based immunochromatographic strip for rapid detection of Rice stripe virus - De-qing Huang; Rui Chen; Ya-qin Wang; Jian Hong; Xue-ping Zhou; Jian-xiang Wu (Journal of Zhejiang University-SCIENCE B, 2019)

A new cinnamic acid glycoside from roots of Heracleum dissectum - Zhi-Gang Wang; Jie Mi; Xin-Rui Wang; Ya-Yu Huo; Ya-Jie Peng; Hai-Min Zhang; Yang Gao; Hai-Long Zhang (Natural Product Research, 2018)

Inhibitory effects of Dioscin on atherosclerosis and foam cell formation in hyperlipidemia rats - Ping Wang; Li-ya He; Guo-dong Shen; Rui-lin Li; Jun-li Yang (Inflammopharmacology, 2017)

Erratum to: Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling‑Ling Zhang; Hu Chen; Mi Luo; Xiao‑Wei Zhang; Mei Deng; Jian Ma; Peng‑Fei Qi; Ji‑Rui Wang; Guo‑Yue Chen; Ya‑Xi Liu; Zhi‑En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling-Ling Zhang; Hu Chen; Mi Luo; Xiao-Wei Zhang; Mei Deng; Jian Ma; Peng-Fei Qi; Ji-Rui Wang; Guo-Yue Chen; Ya-Xi Liu; Zhi-En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

The Research on the Relationship of RAGE, LRP-1, and Aβ Accumulation in the Hippocampus, Prefrontal Lobe, and Amygdala of STZ-Induced Diabetic Rats - Lou-Yan Ma; Yu-Lang Fei; Xiao-Ye Wang; Song-Di Wu; Jun-Hui Du; Mei Zhu; Long Jin; Ming Li; Hai-Long Li; Jia-Jia Zhai; Lu-Peng Ji; Ran-Ran Ma; et al. (Journal of Molecular Neuroscience, 2017)

CGRP 8-37 enhances lipopolysaccharide-induced acute lung injury and regulating aquaporin 1 and 5 expressions in rats - Fu Hong-min; Huangfu Chun-rong; Zheng Rui; Su Li-na; Wang Ya-jun; Li Li (Journal of Physiology and Biochemistry, 2016)

Characterization of the waxy gene in diploid Triticum L. and Aegilops L. species and its geographic distribution - Wei Li; Bang-Bo Fu; Zhe Li; Ya-Xi Liu; Zhi-En Pu; Peng-Fei Qi; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng (Genetic Resources and Crop Evolution, 2016)

Variations of Nutrients in Gross Rainfall, Stemflow, and Throughfall Within Revegetated Desert Ecosystems - Ya-feng Zhang; Xin-ping Wang; Yan-xia Pan; Rui Hu (Water, Air, & Soil Pollution, 2016)

Structure and expression of phosphoglucan phosphatase genes of Like Sex Four1 and Like Sex Four2 in barley - Jian Ma; Shang Gao; Qian-Tao Jiang; Qiang Yang; Min Sun; Ji-Rui Wang; Peng-Fei Qi; Ya-Xi Liu; Wei Li; Zhi-En Pu; Xiu-Jin Lan; Yu-Ming Wei; et al. (Genetica, 2016)

Identification of a Novel Rat NR2B Subunit Gene Promoter Region Variant and Its Association with Microwave-Induced Neuron Impairment - Li-Feng Wang; Da-Wei Tian; Hai-Juan Li; Ya-Bing Gao; Chang-Zhen Wang; Li Zhao; Hong-Yan Zuo; Ji Dong; Si-Mo Qiao; Yong Zou; Lu Xiong; Hong-Mei Zhou; et al. (Molecular Neurobiology, 2016)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Inhibition of IRF3 expression reduces TGF-β1-induced proliferation of hepatic stellate cells - Ming-ming Ni; Tao Xu; Ya-rui Wang; Ying-hua He; Qun Zhou; Cheng Huang; Xiao-ming Meng; Jun Li (Journal of Physiology and Biochemistry, 2016)

Sequence Characteristics and Phylogenetic Implications of the nrDNA Internal Transcribed Spacers (ITS) in Protospecies and Landraces of Sugarcane (Saccharum officinarum L.) - Cui-Feng Yang; Li-Tao Yang; Yang-Rui Li; Ge-Min Zhang; Chun-Ya Zhang; Wei-Zan Wang (Sugar Tech, 2016)

Comparison of diurnal dynamics in evaporation rate between bare soil and moss-crusted soil within a revegetated desert ecosystem of northwestern China - Ya-Feng Zhang; Xin-Ping Wang; Yan-Xia Pan; Rui Hu (Journal of Earth System Science, 2016)

Characterization of genes encoding Starch Branching Enzyme I from Triticum monococcum and its diploid wheat relatives - Xiu-Ying Wang; Chang-Shui Wang; Jian Ma; Ji-Rui Wang; Ya-Xi Liu; Peng-Fei Qi; Wei Li; Zhi-En Pu; Xiu-Jin Lan; Yu-Ming Wei; You-Liang Zheng; Qian-Tao Jiang (Biologia, 2015)

Activation of VEGF/Flk-1-ERK Pathway Induced Blood–Brain Barrier Injury After Microwave Exposure - Li-Feng Wang; Xiang Li; Ya-Bing Gao; Shui-Ming Wang; Li Zhao; Ji Dong; Bin-Wei Yao; Xin-Ping Xu; Gong-Min Chang; Hong-Mei Zhou; Xiang-Jun Hu; Rui-Yun Peng (Molecular Neurobiology, 2015)

Quantitative trait locus mapping for seed dormancy in different post-ripening stages in a Tibetan semi-wild wheat (Triticum aestivum ssp. tibetanum Shao) - Yun-Feng Jiang; Ji-Rui Wang; Wei Luo; Yu-Ming Wei; Peng-Fei Qi; Ya-Xi Liu; Qian-Tao Jiang; Yuan-Ying Peng; Guo-Yue Chen; Shou-Fen Dai; You-Liang Zheng; Xiu-Jin Lan (Euphytica, 2015)

Dependence of shrub canopy water storage on raindrop size in revegetated desert - Xin-ping Wang; Hao Zhang; Ya-feng Zhang; Rui Hu; Yan-xia Pan (Hydrological Sciences Journal, 2015)

Anxiolytic effects of ketamine in animal models of posttraumatic stress disorder - Li-Ming Zhang; Wen-Wen Zhou; Ya-Jun Ji; Ying Li; Nan Zhao; Hong-Xia Chen; Rui Xue; Xin-Guo Mei; You-Zhi Zhang; Heng-Lin Wang; Yun-Feng Li (Psychopharmacology, 2015)

Historical development and future perspectives of Environmental Specimen Bank in China: a mini review - Fang Qiu; Xiang-Zhou Meng; Yan-Ling Qiu; Qing-Hui Huang; Ying Liu; Ling-Ling Wu; Qian-Fen Xiao; Ya-Jie Sun; Rui Wang; Yi-Hui Zhou; Zhen-Yang Yu; Da-Qiang Yin; et al. (Environmental Science and Pollution Research, 2015)

Upregulation of HIF-1α Via Activation of ERK and PI3K Pathway Mediated Protective Response to Microwave-Induced Mitochondrial Injury in Neuron-Like Cells - Li Zhao; Yue-Feng Yang; Ya-Bing Gao; Shui-Ming Wang; Li-Feng Wang; Hong-Yan Zuo; Ji Dong; Xin-Ping Xu; Zhen-Tao Su; Hong-Mei Zhou; Ling-Ling Zhu; Rui-Yun Peng (Molecular Neurobiology, 2014)

Semicarbazide – from state-of-the-art analytical methods and exposure to toxicity: a review - Wen-Rui Tian; Ya-Xin Sang; Xiang-Hong Wang (Food Additives & Contaminants: Part A, 2014)

The influence of Caragana korshinskii shrub on soil and hydrological properties in a revegetation-stabilized desert ecosystem - Yan-Xia Pan; Xin-Ping Wang; Xin-Rong Li; Ya-Feng Zhang; Rui Hu; Hao Zhang (Hydrological Sciences Journal, 2014)

Needle-free injection of insulin powder: delivery efficiency and skin irritation assessment - Chun-yu Li; Zhe-wei Wang; Can Tu; Jia-bo Wang; Bing-qian Jiang; Qi Li; Ling-na Zeng; Zhi-jie Ma; Ping Zhang; Yan-ling Zhao; Ya-ming Zhang; Dan Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Characterization and expression profiles of MaACS and MaACO genes from mulberry (Morus alba L.) - Chang-ying Liu; Rui-hua Lü; Jun Li; Ai-chun Zhao; Xi-ling Wang; Umuhoza Diane; Xiao-hong Wang; Chuan-hong Wang; Ya-sheng Yu; Shu-mei Han; Cheng Lu; Mao-de Yu (Journal of Zhejiang University-SCIENCE B, 2014)

Monitoring and modeling the effects of groundwater flow on arsenic transport in Datong Basin - Qian Yu; Yanxin Wang; Rui Ma; Chunli Su; Ya Wu; Junxia Li (Journal of Earth Science, 2014)

Condensation of water vapour on moss-dominated biological soil crust, NW China - XIN-PING WANG; YAN-XIA PAN; RUI HU; YA-FENG ZHANG; HAO ZHANG (Journal of Earth System Science, 2014)

Shapinggou: the largest Climax-type porphyry Mo deposit in China - Hong Zhang; Cong-Ying Li; Xiao-Yong Yang; Ya-Li Sun; Jiang-Hong Deng; Hua-Ying Liang; Rui-Long Wang; Bo-Hua Wang; Yu-Xian Wang; Wei-Dong Sun (International Geology Review, 2014)

How immunogenetically different are domestic pigs from wild boars: a perspective from single-nucleotide polymorphisms of 19 immunity-related candidate genes - Shanyuan Chen; Rui Gomes; Vânia Costa; Pedro Santos; Rui Charneca; Ya-ping Zhang; Xue-hong Liu; Shao-qing Wang; Pedro Bento; Jose-Luis Nunes; József Buzgó; Gyula Varga; et al. (Immunogenetics, 2013)

Heterogeneity of soil surface temperature induced by xerophytic shrub in a revegetated desert ecosystem, northwestern China - YA-FENG ZHANG; XIN-PING WANG; YAN-XIA PAN; RUI HU; HAO ZHANG (Journal of Earth System Science, 2013)

Meso-Cenozoic extensional structures in the Northern Tarim Basin, NW China - Yue-Jun Li; Yan Zhao; Long-De Sun; Wen-Jie Song; Duo-Ming Zheng; Ya-Lei Liu; Dao-Xuan Wang; Jian-Feng Hu; Qi-Rui Zhang (International Journal of Earth Sciences, 2013)

Erratum to: Erythrobacter westpacificensis sp. nov., a Marine Bacterium Isolated from the Western Pacific - Jingjing Wei; Yujiao Mao; Qiang Zheng; Rui Zhang; Ya-Nan Wang; Nianzhi Jiao (Current Microbiology, 2013)

Erythrobacter westpacificensis sp. nov., a Marine Bacterium Isolated From the Western Pacific - Jingjing Wei; Yujiao Mao; Qiang Zheng; Rui Zhang; Ya-Nan Wang (Current Microbiology, 2013)

Diurnal and seasonal variations of surface albedo in a spring wheat field of arid lands of Northwestern China - Ya-feng Zhang; Xin-ping Wang; Yan-xia Pan; Rui Hu (International Journal of Biometeorology, 2013)

Meta-analysis of QTL associated with tolerance to abiotic stresses in barley - Wei-Tao Li; Chunji Liu; Ya-Xi Liu; Zhi-En Pu; Shou-Fen Dai; Ji-Rui Wang; Xiu-Jin Lan; You-Liang Zheng; Yu-Ming Wei (Euphytica, 2013)

Overexpression of a Transcription Factor OsMADS15 Modifies Plant Architecture and Flowering Time in Rice (Oryza sativa L.) - Sun-Jie Lu; He Wei; Ya Wang; Hui-Mei Wang; Rui-Fang Yang; Xiao-Bo Zhang; Ju-Min Tu (Plant Molecular Biology Reporter, 2012)

Quaternary palaeoenvironmental oscillations drove the evolution of the Eurasian Carassius auratus complex (Cypriniformes, Cyprinidae) - Yun Gao; Shu‐Yan Wang; Jing Luo; Robert W. Murphy; Rui Du; Shi‐Fang Wu; Chun‐Ling Zhu; Yan Li; Andrei D. Poyarkov; Sang Ngoc Nguyen; Peng‐Tao Luan; Ya‐Ping Zhang (Journal of Biogeography, 2012)
Aim We sought to reconstruct the spatio‐temporal genetic diversification in goldfish of the Carassius auratus complex, which is widely distributed in Eurasia, to test whether vicariance events or human‐mediated translocations best explained lineage divergence and genogeographical history. Location East Asia and the Oriental islands including Japan, the Ryukyus and Taiwan, and Europe, including Russia and the Czech Republic. Methods We reconstructed the matrilineal history of Eurasian goldfish using 1876 sequences from the partial mitochondrial DNA control region (426 bp) and 191 complete sequences of cytochrome b (1140 bp) from 67 localities representing most of the range of the species. Divergence times were estimated using a Bayesian Markov chain Monte Carlo approach based either on molecular clock data or on the fossil record. Genetic structure and the historical demography of populations were analysed using partial correlation tests and analyses of molecular variance. Results Three lineages had high levels of regional specificity. Lineages A and B from the main islands of Japan differed greatly from lineage C, which occurred on the mainland, Taiwan and the Ryukyus. Lineages A and B had late Pliocene origins. Six geographically constrained sublineages within lineage C had near‐simultaneous mid‐Pleistocene divergences. Main conclusions Genetic structure in the C. auratus complex appears to have been driven by palaeoenvironmental perturbations rather than human translocations. The disappearance of a land bridge in the Tsushima Strait around 3.0 Ma is responsible for the separation of Japanese and continental lineages; the estimated divergence time is 2.75–2.32 Ma. Fujian, China and Vietnam appear to have provided important refugia for the C. auratus complex during glaciation. After warm, moist summer monsoons intensified during the mid‐Pleistocene, goldfish are likely to have dispersed north‐eastwards to recolonize the Ryukyus via Taiwan and northwards to recolonize mainland China.

Polymorphisms in the XPG gene and risk of gastric cancer in Chinese populations - Jing He; Li-Xin Qiu; Meng-Yun Wang; Rui-Xi Hua; Ruo-Xin Zhang; Hong-Ping Yu; Ya-Nong Wang; Meng-Hong Sun; Xiao-Yan Zhou; Ya-Jun Yang; Jiu-Cun Wang; Li Jin; et al. (Human Genetics, 2012)

He and Ar isotopic compositions and genetic implications for the giant Shizhuyuan W–Sn–Bi–Mo deposit, Hunan Province, South China - Li-Yan Wu; Rui-Zhong Hu; Jian-Tang Peng; Xian-Wu Bi; Guo-Hao Jiang; Hong-Wei Chen; Qiao-Yun Wang; Ya-Ying Liu (International Geology Review, 2011)

Identification of low abundance polyA-binding proteins in Arabidopsis chloroplast using polyA-affinity column - Rui-Juan Ni; Zhuo Shen; Chuan-Ping Yang; Ya-Dan Wu; Ying-Dong Bi; Bai-Chen Wang (Molecular Biology Reports, 2010)

Involvement of the ornithine decarboxylase/polyamine system in precondition-induced cardioprotection through an interaction with PKC in rat hearts - Ya-Jun Zhao; Wei-Hua Zhang; Chang-Qing Xu; Hong-Zhu Li; Li-Na Wang; Hong Li; Yi-Hua Sun; Yan Lin; Li-Ping Han; Li Zhang; Yie Tian; Rui Wang; et al. (Molecular and Cellular Biochemistry, 2009)

Loop-mediated isothermal amplification for rapid detection of Bacillus anthracis spores - Yan-Mei Qiao; Yong-Chao Guo; Xian-En Zhang; Ya-Feng Zhou; Zhi-Ping Zhang; Hong-Ping Wei; Rui-Fu Yang; Dian-Bing Wang (Biotechnology Letters, 2007)

Pedoecological effects of a sand-fixing poplar (Populus simonii Carr.) forest in a desertified sandy land of Inner Mongolia, China - Feng-Rui Li; Hua Zhang; Li-Ya Zhao; Yasuhito Shirato; Xian-Zhi Wang (Plant and Soil, 2003)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)